Nitrous Oxide Concentrations from Discrete Samples during MSM18/2 - Annette Kock; Damian L Arévalo-Martínez; Hermann W Bange (PANGAEA, 2019)
Depth profile measurements of nitrous oxide; triplicate samples were taken from the CTD rosette and analyzed by static headspace equilibration and manual injection into a GC-ECD system.